Peran Guru Pendidikan Agama Islam dalam Membentuk Nilai-Nilai Karakter Siswa di SMA Negeri 1 Ngimbang - Elis Sari; M. Rizal Rizqi; Hj. Khotimah Suryani (LPPM Institut Pendidikan Nusantara Global, 2026)
Character education is a component of the educational the system aimed at forming students who possess noble character, responsibility, and positive personality traits. Teacher of Islamic religiouseducation play a crucial role in molding charakter education ideal in pupils through learning activities and habituation programs within the school environment. This study seeks to explain the function of Islamic religious education instructors in instilling personality education values in students at SMA Negeri 1 Ngimbang and to determine the obstacles and solutions when it’s implemented. This study employs a qualitative method using a descriptive method. Information were gathered by interviews, observation and documentation. The findings indicate that Islamic Religious Education teacher serve as instructors, role models, mentors and motivators when it comes to fostering moral principles like respect for one another, discipline, religion and accountability. The cultivation of these values is carried out through classroom learning, teacher role modeling, positive behavior habituation, and religious activities at school. However, several obstacles were found, including the impact of students' social environment, time constraints for learning and the effects of social media and technology advancements. Therefore, for character education to be successful and for pupils to internalize these principles as best they can, cooperation between educators, school and parents is required.